The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1001/jama.1995.03530020083037
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization for Femoropopliteal Disease

Abstract: Angioplasty is the preferred initial treatment in patients with disabling claudication and a femoropopliteal stenosis or occlusion and in those with chronic critical ischemia and a stenosis. Bypass surgery is the preferred initial treatment in patients with chronic critical ischemia and a femoropopliteal occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(21 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Our findings build on the analysis by Hunink and colleagues, who compared endovascular therapy and surgical bypass using a Markov model and literature-based estimates [5]. Compared to the findings by Hunink and colleagues, we found a smaller difference in QALMs between endovascular therapy and surgical bypass.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings build on the analysis by Hunink and colleagues, who compared endovascular therapy and surgical bypass using a Markov model and literature-based estimates [5]. Compared to the findings by Hunink and colleagues, we found a smaller difference in QALMs between endovascular therapy and surgical bypass.…”
Section: Discussionsupporting
confidence: 80%
“…In these cases, the patient could choose to repeat the initial procedure or to undergo one of the remaining three therapies, which were constructed as “clones” of the initial branch on the tree diagram. We assumed each patient would undergo each procedure a maximum of two times [5]. Additionally, we assumed that patients who initially chose medical management would not later opt for a surgical procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly critical leg ischemia (PAD stages III–IV) is on average $4478 more expensive than the treatment of intermittent claudication (PAD stage II disease) [8,9]. This also holds true for the costs of a specific therapeutic/invasive procedure; for example, the costs for percutaneous transluminal angioplasty (PTA) are much greater for patients with critical ischemia and tissue necrosis than for patients with disabling claudication secondary to higher complication rates and longer hospital stays [10]. Another consideration is that amputation has been shown to be about twice as expensive as a limb salvage strategy with either interventional or surgical methods and for both acute and chronic limb threatening ischemia [11].…”
Section: Factors That Impact the Costs Of Peripheral Vascular Disementioning
confidence: 99%
“…Initial angioplasty increased quality-adjusted life expectancy by 2 to 13 months in patients with disabling claudication and by 1 to 4 months in patients with chronic critical ischemia and resulted in decreased lifetime expenditures compared with bypass surgery in both groups. A Markov model economic estimation based on this study using a maximum threshold cost of US$50,000 per QALY showed that PTA was cost effective when compared with vein bypass for lesions that could be treated with a better than 30% 5-year patency [10]. …”
Section: Cost Effectiveness Of Percutaneous Transluminal Angioplasmentioning
confidence: 99%
“…Similarly, a cost-effectiveness analysis compared PTA and bypass surgery with exercise therapy for treatment of claudication and demonstrated that the cost-effectiveness for PTA was $38,000 per quality-adjusted life year compared to $311,000 per quality-adjusted life year for bypass surgery [88]. In regards to cost-effectiveness, PTA is preferable to surgery as long as the expected 5-year patency rate for the treated vessel exceeds 30% [89]. In addition, PTA is preferred over surgery, when possible, in patients younger than 50 years old, because they have a higher risk of graft failure after surgical therapy than do older patients [1].…”
Section: Managementmentioning
confidence: 99%